STRATEGI KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN STANDAR NASIONAL PENDIDIKAN (SNP) PADA SMK NEGERI 2 BUKITTINGGI - Sriwahyuni, Eci; Kristiawan, Muhammad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
The Issue in this paper was implementation of National Education Standards has not revealed. The informants were 17 person. The data collection was the researchers as a key instrument and supporting instruments were interview, observation guidelines, field notes, camera and HP. Data collection techniques using the participant observation, in depth interview and documentation study. Data were analyzed using models Miles and Huberman. The testing of the data validity using triangulation sources, techniques and timing. The finding revealed that in the implementing the content standards by established curriculum development team to collaborate with the business community in the curriculum development process. In implementing the process standards by implemented learning process based on Information and Technology (IT). In implementing the competency standards by improved the academic and non academic achievement, motivated the entrepreneurial spirit through the production unit and training in industry. In implementing the standards of teachers and staffs by improved the competence of teachers and staffs through training. In implementing the standards of facilities by planning, procurement, maintenance and inventory of school facilities. In implementing the  management standards by arranged a school program (RKS) and school budget activity program (RKAS), formulated and socialized the vision and mission of the school. In implementing the financing standards by planning, managing and reporting of school funding. In implementing assessment standards by using Information and Technology (IT) in the assessment